Carney complex: a case with thyroid follicular adenoma without a PRKAR1A mutation - Shinji Hattori; Yukou Yamane; Ryoichi Shimomura; Yuki Uchida; Nobuhiko Toyota; Yoshio Miura; Setsujyo Shiota; Yoshitsugu Tajima (Surgical Case Reports)
Abstract Background Carney complex (CNC) is a very rare disease. Although thyroid lesions are included in the diagnostic criteria for CNC, they are an infrequent occurrence. Case presentation The patient was a 69-year-old woman who had undergone the removal of a left atrial myxoma 10 years earlier, at the age of 59. At the time of the operation, thyroid ultrasonography (US) revealed multiple hypoechoic nodules. Thyroid scintigraphy revealed an increased uptake of 99mTc in these lesions, which was consistent with toxic multinodular goiter, and she was diagnosed with CNC. Genetic studies showed no mutation in the PRKAR1A (protein kinase A regulatory subunit 1-α) gene. From then on, she received annual brain magnetic resonance imaging (MRI), abdominal computed tomography (CT), and thyroid US examinations. Her follicular thyroid nodules gradually increased in number and size. Although aspiration cytology samples from the thyroid nodules diagnosed them as class III, thyroid cancer could not be ruled out. The patient underwent a partial thyroidectomy, and the pathological diagnosis was multiple follicular adenomas. Conclusion Careful and frequent evaluation of the thyroid gland should be required for CNC patients due to the potential for carcinoma to develop in the context of a variety of follicular thyroid lesions.